2016
DOI: 10.1007/978-3-319-42044-8_28
|View full text |Cite
|
Sign up to set email alerts
|

mFast-SeqS as a Monitoring and Pre-screening Tool for Tumor-Specific Aneuploidy in Plasma DNA

Abstract: Recent progress in the analysis of cell-free DNA fragments (cell-free circulating tumor DNA, ctDNA) now allows monitoring of tumor genomes by non-invasive means. However, previous studies with plasma DNA from patients with cancer demonstrated highly variable allele frequencies of ctDNA. Comprehensive genome-wide analysis of tumor genomes is greatly facilitated when plasma DNA has increased amounts of ctDNA. In order to develop a fast and cost-effective pre-screening method for the identification of plasma samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Our study shows that an increase in tumor fraction in the plasma by LP-WGS likely reflects tumor progression. Because it is time-and cost-effective, LP-WGS can also be used as an initial quality control step to determine tumor fraction and select only the samples with high tumor fraction to perform target enrichment and deep sequencing (15,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study shows that an increase in tumor fraction in the plasma by LP-WGS likely reflects tumor progression. Because it is time-and cost-effective, LP-WGS can also be used as an initial quality control step to determine tumor fraction and select only the samples with high tumor fraction to perform target enrichment and deep sequencing (15,20).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 15 years, NGS technology has evolved rapidly and is playing an increasingly important role in cancer research and clinical studies (19). It has been shown that low-pass whole-genome sequencing (LP-WGS) was capable of identifying both focal and broad CNVs in cfDNA from patients with cancer (15,20).…”
Section: Introductionmentioning
confidence: 99%
“…During a median follow-up period of 6 months (range 0.4-19.2), serial plasma samples (median 5, range 2-21) were collected before and during treatment. mFAST-SeqS was used as an initial measure of tumor content [20,37]. For all samples, the median genome-wide z-score was 1.0 (range − 0.9-58.0), and an elevated z-score was observed in 19/252 samples (7.5%) from 9 patients.…”
Section: Longitudinal Analysis Of Ctdna In Renal Tumorsmentioning
confidence: 99%
“…Thus, genetic heterogeneity between tumours will be a major limitation for targeted approaches. Analysis of CNAs interrogates the whole genome in a single test method, but often requires at least 3%–10% tumour fraction in plasma cfDNA for reliable detection . It is less likely that early‐stage tumours will shed this much ctDNA.…”
Section: Difficulties and Limitations Of Ctdna Analysismentioning
confidence: 99%